Pobreza, Medio Ambiente y Desarrollo Sostenible - Angulo Sánchez , Nicolás (Nómadas. Critical Journal of Social and Juridical Science, 2010)
When we speak of human development and the reduction of poverty, we must not refer to the unleashed consumption of goods (from cars, computers, increasingly powerful cell phones down to an almost unlimited variety of any product), but to the fact that every human being should be able to satisfy his basic needs of food, health care, housing, education, for example, as well as having enough leisure time to enjoy culture and the arts, carry out enriching social relations, make our legitimate vocations come true in any field we chose, and also have enough time to rest. This is an idea of human richness, and therefore of poverty, which goes much further than the field of economy and its monetary or commercial evaluation.